Microbiota Modulates the Immunomodulatory Effects of Filifolinone on Atlantic Salmon - Modak-Canobra, B; Tello-Reyes, M; Vargas-Cardenas, R; Valdes-Parra, N; Parra-Mardonez, N; Espinoza-Majmud, D (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Filifolinone is an aromatic geranyl derivative, a natural compound isolated from Heliotropum sclerocarpum, which has immunomodulatory effects on Atlantic salmon, upregulating cytokines involved in Th1-type responses through a mechanism that remains unknown. In this work, we determined whether the immunomodulatory effects of filifolinone depend on the host microbiotic composition. We evaluated the effect of filifolinone on immune genes and intestinal microbiotic composition of normal fish and fish previously treated with bacitracin/neomycin. Filifolinone induced the early expression of IFN-α1 and TGF-β, followed by the induction of TNF-α, IL-1β, and IFN-γ. A pre-treatment with antibiotics modified this effect, mainly changing the expression of IL-1β and IFN-γ. The evaluation of microbial diversity shows that filifolinone modifies the composition of intestinal microbiota, increasing the abundance of immunostimulating organisms like yeast and firmicutes. We identified 69 operational taxonomic units (OTUs) associated with filifolinone-induced IFN-γ. Our results indicate that filifolinone stimulates the immune system in two ways, one dependent on fish microbiota and the other not. To our knowledge, this is the first report of microbiota-dependent immunostimulation in Salmonids. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.